“Contractual” reflections on Chile’s law on voluntary pregnancy termination - Caro-Miranda, José Javier (Acta Bioethica, 2019)
After one year of the Law of Voluntary Interruption of Pregnancy in Chile, the possibility of aborting in three specific situations is recognized and professional support is given to the women who invoke it. Reflections are raised about its application in the causes described in it. Human dignity is placed as the central axis of the interpretation of the fetus-maternal reality. The meaning of the medical-perinatal act is discussed in the context of the preservation of the human species. The application of the principle of double effect and that of the only possible good in the discernment of the first causal is explained. In the second case, the influence of technology in fetal anamorphosis is discussed, together with the vulnerability and self-referential maternal focus in the malformed fetus. In the third case, we try to apply the notion of how violence cannot justify itself and we need to mediate consensus so as not to focus on the fetus as the cause of the harm. The aim is to warn about the risk of alienation of health professionals before the meaning of the dignity of the human being.